Defining reverse and green supplier selection criteria with a strategic management approach - Akkartal, Gonca Reyhan; Mızrak, Filiz (Springer Science and Business Media Deutschland GmbH, 2023)
Today, the environmental problems that emerged over time because of industrialization and globalization and the depletion of natural resources have forced businesses and managers to consider environmental factors while determining their management styles. From this perspective, businesses try to add not only economic value but also ecological value to all their activities to increase their environmental performance. Businesses do this by integrating green activities into all their components in the supply chain network and collaborating with suppliers who care about the environment. However, in the realization of environmental awareness and its increasing importance for companies, green and reverse suppliers create budget constraints for businesses and choosing all of them at the same time is extremely challenging financially. In this context, the aim of this study is to reveal the criteria to be considered when choosing reverse and green suppliers by benefiting from the current literature and to shed light on the strategies that companies should develop when choosing suppliers.
Keywords: Reverse Logistics; Strategic Management; Supply Chain Management